2023
DOI: 10.1161/hypertensionaha.122.20018
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Pills and Hypertension: A Review of Current Evidence and Recommendations

Abstract: Oral contraceptive pills (OCPs) have been used as effective and popular forms of contraception since the middle of the last century. By 2019, over 150 million reproductive-aged individuals were using OCPs to prevent unintended pregnancies worldwide. Safety concerns regarding the effects of OCPs on blood pressure were reported soon after these pills gained approval. Although OCP doses were subsequently reduced, epidemiologic evidence continued to support a smaller, but significant association between OCPs and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 104 publications
0
7
0
3
Order By: Relevance
“…Regarding to Hypertension oral contraceptives frequently causes a mild elevation in blood pressure within the normal range; however, overt hypertension can occur [13].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to Hypertension oral contraceptives frequently causes a mild elevation in blood pressure within the normal range; however, overt hypertension can occur [13].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in BP is related to a rise in hepatic production of angiotensinogen, activation of the RAAS, an increase in vascular resistance, and a decrease in circulating nitric oxide (NO). 2,6…”
Section: Adolescence and Early Adulthoodmentioning
confidence: 99%
“…Available epidemiological studies of high dose estrogen use found a mean elevation in BP of 3 to 6 mmHg, and cessation of estrogen use typically led to return of BP to baseline ranges [10,11]. Lower estrogen doses, however, as seen in postmenopausal hormone therapy, have revealed a much lower association with HTN [12].…”
Section: Oral Contraceptives Pillsmentioning
confidence: 99%
“…Although, a disproportionately higher rate of RH in the African American population has been suggested to have a genetic predisposition and associated with a particular CYP3A5 enzyme (11β-hydroxysteroid dehydrogenase type 2), which plays a role in metabolism of cortisol, particularly in the kidney [11].…”
Section: Genetic Componentsmentioning
confidence: 99%